(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the role of family environment in shaping individual stress resilience and work motivation. Family, as a primary socialization agent, significantly impacts the development of coping strategies, emotional regulation, and the formation of motivational attitudes toward professional activity. The study examines theoretical frameworks and empirical findings that highlight how parental support, family cohesion, communication patterns, and emotional climate contribute to adaptive functioning and occupational engagement. A scientific table presents key determinants of stress resilience and work motivation, followed by a detailed discussion of their implications. The findings underscore the importance of positive family dynamics for fostering psychological resources essential for career development and overall well-being